REGULASI PEMINDAHAN IBUKOTA NEGARA REPUBLIK INDONESIA BERDASARKAN KONSTITUSI - Errangga (2020)
At the end of April 2019, the President announced to move the state capital away from Java based on various considerations, especially regarding the decrease in the environmental carrying capacity of the island of Java, particularly in Jabodetabekpunjur (Jakarta - Bogor - Depok - Tangerang - Bekasi - Puncak - Cianjur). The location of the prospective state capital was officially announced on August 26, 2019, namely North Penajam Paser Regency and part of the Kutai Kartanegara Regency in East Kalimantan. However, the regulation on the state capital relocation has not been specifically regulated so far. This raises problems, Which is about the constitutionality of the state capital relocation and its legal fundament. This research is a normative juridical study with a legislative, theoretical, and comparative approach. Aims to study the constitutionality of the state capital relocation and its legal fundament establishment. The results of the research showed that the relocation of the state capital is a constitutional act as long as in each stage of its implementation, it did not violate the norms contained in the constitution and implemented by forming the legal fundament first.